2018
DOI: 10.21534/ai.v18i2.107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Probiotic Bacillus sp. D2.2 and Prebiotic Sweet Potato Extract on Growth Performance and Resistance to Vibrio harveyi in Pacific white shrimp, Litopenaeus vannamei

Abstract: In this study, the effects of oral administration of probiotic Bacillus sp. D2.2 and prebiotic from sweet potato extract on growth performance and resistance against Vibrio harveyi in Pacific white shrimp (Litopenaeus vannamei) were investigated. During 32-day feeding experiment, 360 individuals of Pacific white shrimp (PL15) with initial weight of 0.02 ± 0.002 g were fed with basal diet as control (A); supplemented with 6% probiotic and 0% prebiotic (B); 6% probiotic and 2% prebiotic (C); 6% probiotic and 4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Ramadhani et al 285 reported that synbiotic intervention resulted in the highest SGR of shrimps at 31%, which was significantly different from that of the probiotics (28.8%), prebiotics (26.9%) and the control group (27.6%). Furthermore, this result is also consistent with the findings of Harpeni et al, 58 which demonstrated the synbiotic combination of Bacillus sp . and sweet potato extract prebiotics lowered the FCR and contributed to total weight gain.…”
Section: Synbioticssupporting
confidence: 93%
See 2 more Smart Citations
“…Ramadhani et al 285 reported that synbiotic intervention resulted in the highest SGR of shrimps at 31%, which was significantly different from that of the probiotics (28.8%), prebiotics (26.9%) and the control group (27.6%). Furthermore, this result is also consistent with the findings of Harpeni et al, 58 which demonstrated the synbiotic combination of Bacillus sp . and sweet potato extract prebiotics lowered the FCR and contributed to total weight gain.…”
Section: Synbioticssupporting
confidence: 93%
“…Their immunostimulating potentials are reflected in increased immune‐related gene expression and enhanced survival rates in challenge tests using common pathogens 127‐130 . Intriguingly, the effect in promoting animal growth was also evident in the treated cohorts 50,58‐60,131,132 . It was postulated that the growth promotion effect is multifactorial, which is dependent on the treatment type.…”
Section: Bacterial‐derived Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…as a probiotic in shrimp culture improved resistance performance of Pacific white shrimp (Litopenaeus vannamei) against V. harveyi. Probiotic applications significantly improved shrimp growth parameters such as weight gain, average daily growth, feed conversion ratio, and survival rate than those of the control against V. harveyi (Harpeni et al 2018). However, information on the characteristic of the antimicrobial compounds produced by the indigenous Bacillus spp.…”
Section: Introductionmentioning
confidence: 95%
“…Bacterial strains and media Bacillus sp. D2.2 isolated from traditional tiger shrimp in East Lampung (Setyawan et al, 2014) was inoculated on seawater complete-agar (SWC, 5 g bacto peptone (Oxoid, England), 1 g yeast extract (Oxoid, England), 3 ml glycerol, 15 g bacto agar (Oxoid, England), 750 ml seawater, and 250 ml The Growth Kinetisc of Bacillus D2.2 649 distilled water) and then transferred to SWC-broth (without agar) with rotary shaker at 140 rpm for 24 h at 30°C (Harpeni et al, 2018). V. alginolyticus, A. hydrophila, and S. aureus were bacterial collections of the Laboratory of Fisheries Culture, Department of Aquaculture, University of Lampung and cultured on trypticase soy agar (TSA) medium (Oxoid, England).…”
Section: Materi Dan Metodementioning
confidence: 99%